2023
DOI: 10.1002/acr2.11556
|View full text |Cite
|
Sign up to set email alerts
|

Real‐World Evidence Assessing Psoriatic Arthritis by Disease Domain: An Evaluation of the CorEvitas Psoriatic Arthritis/Spondyloarthritis Registry

Abstract: ObjectiveReal‐world studies assessing treatment response by psoriatic arthritis (PsA) domains are limited. This study aimed to describe the patient characteristics, frequency and combinations of disease domains, disease activity, and patient‐reported outcomes (PROs) by PsA domains in patients who initiated treatment with a tumor necrosis factor inhibitor (TNFi) or interleukin‐17 inhibitor (IL‐17i).MethodsAdults with PsA who initiated treatment with a TNFi or an IL‐17i between January 2013 and January 2021 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… Lubrano et al (2023) reported that IL-17Ai and JAKi could be applied for axial disease treatment in PsA. Besides, among 14% of patients, peripheral arthritis, skin disease and nail psoriasis are the most common combination of PsA domains, and IL-17 inhibitors exhibited effectiveness across all domains ( Mease et al, 2023 ). Future studies should pay more attention to these PsA domains and improve reporting of corresponding data.…”
Section: Discussionmentioning
confidence: 99%
“… Lubrano et al (2023) reported that IL-17Ai and JAKi could be applied for axial disease treatment in PsA. Besides, among 14% of patients, peripheral arthritis, skin disease and nail psoriasis are the most common combination of PsA domains, and IL-17 inhibitors exhibited effectiveness across all domains ( Mease et al, 2023 ). Future studies should pay more attention to these PsA domains and improve reporting of corresponding data.…”
Section: Discussionmentioning
confidence: 99%